2012
DOI: 10.2147/opth.s36968
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the cytotoxicity of six anti-inflammatory eyedrops in four cultured ocular surface cell lines, as determined by cell viability scores

Abstract: PurposeAnti-inflammatory eyedrops are often used in the treatment of corneal epithelial disorders. In the present study, we evaluated the cytotoxicity of six anti-inflammatory eyedrops in four ocular surface cell lines.MethodsThe cytotoxicity of six commercially available anti-inflammatory ophthalmic solutions (ie, diclofenac, bromfenac, pranoprofen, betamethasone, and fluoromethorone) was assessed in three corneal cell lines and one conjunctival cell line. Cell viability was determined by the 3-(4,5-dimethyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…The situation of release in PBS was also tested and it was similar with in DI water ( Figure S6 ). As reported, the bromfenac sodium had some potential side effects of cornea damage 42 and conjunctiva damage 43 , while the sustained release of the drug could reduce the side effects 44 .…”
Section: Resultsmentioning
confidence: 77%
“…The situation of release in PBS was also tested and it was similar with in DI water ( Figure S6 ). As reported, the bromfenac sodium had some potential side effects of cornea damage 42 and conjunctiva damage 43 , while the sustained release of the drug could reduce the side effects 44 .…”
Section: Resultsmentioning
confidence: 77%
“…PPF, one of NSAIDs, is considered to be a major causative factor of ocular surface disorders during keratitis treatment (Ayaki et al, 2012). Therefore, it will be of great importance to access its endothelial cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there have also been reports on side effects of PPF, including irritation, conjunctival congestion, itching, and palpebral edema (Zhu et al, 2009). And it has been found that eyedrops containing NSAIDs exhibited greater cytotoxicity to rabbit and bovine corneal epithelial cells even than those containing steroids with benzalkonium at comparable concentrations (Ayaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reflect the actual situation, we have tried to improve cytotoxicity assays for ocular cells by conducting comprehensive investigations covering a variety of concentrations and treatment times, and based on our studies, we proposed the use of a cell viability score (CVS) as a simple parameter to express the cytotoxic potential of ophthalmic solutions. 2124…”
Section: Cell Viability Score (Cvs) As a Good Indicator Of Ophthalmicmentioning
confidence: 99%